Influence of the resin cement thickness on the fatigue failure loads of CAD/CAM feldspathic crowns - May, Liliana Gressler; Kelly, J. Robert; Bottino, Marco Antonio [UNESP]; Hill, Tom (Elsevier B.V., 2015)
Objectives, to evaluate the influence of the occlusal resin cement thickness on the cyclic loads-to-failure of feldspathic crowns and to compare the results to data from monotonic tests. A large range of cement thickness (50 mu m and 500 mu m) was tested, in order to better measure the influence of this variable. Methods. Feldspathic ceramic crowns (Vita Mark II blocks, Vita Zahnfabrik) were bonded to dentin analog dies (G10 (NEMA grade G10, International Paper), with occlusal resin cement thicknesses of 50 mu m and 500 mu m (Multilink Automix, Ivoclar). The dies were prepared with microchannels for water transport to the cement layer. After 96-h water storage, the specimens (n=20) were submitted to cyclic loads (500,000 cycles at 20 Hz; initial maximum load = 40% of monotonic load, from previous data) following a staircase sensitivity design (step size = 25 N). Failure loads at 500,000 cycles were compared to monotonic failure loads (from a previous study with specimens produced by the same author, using the same materials, specimen configuration and cementation protocol). Results. Crowns with an occlusal cement layer of 50 mu m were more resistant than those cemented with 500 mu m (246.4 +/- 22.9 N vs. 158.9 +/- 22.9 N), under wet cyclic testing conditions (p < 0.001). The fatigue failure loads were reduced compared to monotonic loads: to 37% of monotonic for SO mu m; to 53% of monotonic for 500 mu m. Significance. An occlusal cement thickness of 50 mu m was more favorable for the structural performance of feldspathic crowns than was 500 mu m. Cyclic fatigue reduced failure loads well below those found under monotonic loading. (C) 2015 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Ceramic; Crowns; Cement thickness; Failure load; Fatigue